(untitled) (Fiep Bulletin - online, 2011)
With the aging process a reduction in some physical capacities in the elderly people can be seen, one of them and very important is the agility. This reduction can mean an increase the fall risks, difficulty in do fast movements with direction and way changes. The increase of these risks the dependence of the elderly to other people can also increase. OBJECTIVE - the objective of this study was to verify the effects of an 9 week water resistance training in sedentary elderly women. METODOLOGY - 23 elderly women were randomly selected to participate of the study. They were divided into two groups: experimental (GE; n=19) and control (GC; n=4). Both groups did the timed up and go test (TUG). The test was get up in a signal, walk 3 meters make a turn, get back and sit down again, as fast as they could. The experimental group did 9 week water resistance training. After this 9 week training, both groups did the TUG again. Variance analysis (ANOVA) was used to test the differences inter and intra groups and paired -t test was used to compare differences between intra group pre and post tests, the statistical significance level was set at p < 0.05.. RESULTS - the data analysis was done in a descriptive way, pre (9,66±1,96) and post (7,79±1,20). The value of p=0,000 shows a significant difference between the values. Due to the death of the experimental group, a comparison between the groups was not possible. CONCLUSION - the results of the study (p=,000) shows that an 9 week water resistance training was efficient to improve the agility levels in the sedentary elderly women, in this way reducing some risks related with the aging process.